How does mobile apps’ e-service quality impact customer loyalty? : investigating the effect of customer satisfaction within the purchase experience - Rosa, Jéssica Tatiana Ferreira (2019)
Consumers are changing their shopping habits, influenced by continuously changing technology and new opportunities that take less time to customers and do not force them to be in a specific place at a certain time. Therefore, it is important to understand which factors are important to customers experience while buying online and indicate to managers which characteristics are customers looking for in a mobile app while they are shopping and at the same time, which have a stronger impact on customer satisfaction and loyalty towards the retailer. A cross-section survey was conducted to explore which e-Service quality characteristics represent a stronger impact on Customer Loyalty, taking as example Zara and Mango’s mobile apps, which are well-known worldwide and impact a wide group of online shoppers. Additionally, a characterization of who are these customers using mobile apps to shop was done enabling managers to target their interactions according to customers demographics adapting the message and channels used to establish a better communication. Findings indicate that mobile app design is a key factor that impacts customer satisfaction and loyalty, on top of this, privacy, return handling policies and price offerings are characteristics that customers are looking for while shopping online. Moreover, women between 18-34 years old have a greater predisposition to buy online.